Descentramento e multiplicidade do sujeito na poesia de Paulo Leminski - Nascimento, Lidiane Alves do (2014)
This study investigates the decentering of the modern subject and its implications in poetry and, more closely , the poetry of Paulo Leminski . In light of some theoretical premises about the concept of the subject , from the ancient to modern, we analyze how they historically make up the notion of " poetic self ", from the traditional representative subject to the split subject appearing in the setting of modern poetry . Starting in the first chapter with reflections on the constitution of the subject and the transformations that happened during modernity , we discussed in the second chapter , the problem that lies with the modern lyrical subjectivity, which would have ruined the idea of subjectivity and lyricism as conceived by Hegel . However, the Hegelian concepts in relation to the establishment of an essential identity between empirical subject and the subject introduced in the poem , as well as the acclaim of the true lyric poet as one who lives in himself , singing a song of personal manifestation , having been disseminated ideas and canonized throughout the twentieth century , become the starting point for discussions of the subject and its transformations in modern literature , since the romantics . Our look at the poetry of Leminski prioritizes an analysis of the transformations of the poetic subject , how it is configured , how it questions itself , questioning also the language at the same time. Leminski’s poetry, among many things, reveals the multiplicity of a subject that is not fixed, but moves constantly , turning poetry into a space which describe the attempt to rediscover its individuality , to create a proper diction , without losing the multiplicity that desires " get out of itself". In the third chapter we read the creative work of Leminski intending, departing from decentralization and multiplicity, to investigate the facets of a split subject in books Caprichos e relaxos (1983), Distraídos venceremos (1987), La vie en close (1991), Winterverno (1994) e O ex-estranho (1996), and examine aspects such as the dispersion of the subject, the identity crisis plaguing the modern world, unstable modes, fluid and discontinuous "being." In Leminski , avoidance of intimate voice of the poet, traditionally recognized as one that emits individual and deep feelings of the artist's soul, gives way to the plurality of voices to inhabit the ironic poetic speech of his verses. Furthermore , there is an encounter between the subject and the things of the world consolidated the work of language, allowing the transition from individual to collective.